The Management of Torus Mandibularis and Maxillary Buccal Exostosis before Loading Single Complete Denture and Removable Partial Denture - Tawkaew U (Journal of The Department of Medical Services, 2021)
Generally management of buccal exostosis and torus mandibularis is periodic monitoring. Surgical removal is indicated only when their sizes have negatively impacted periodontium, esthetics, interfered with mastication, speech or prosthesis, induced ulcer and impaired healing. Surgical removal may also be considered in a case where bone graft is required on other sites. 72 year old patient who had recieved a preprosthetic surgical removal of left maxillary buccal exostosis and lower left and right torus mandibularis was reported. Maxillary buccal exostosis was “removed” via wedge-shaped mid alveolar ridge bone removal and compression of cortical plate to achieve desirable alveolar ridge shape. This was done instead of direct torus removal to preserve cortical bone and minimize the risk of further bone resorption. Upper single denture and lower removable partial denture were made after surgery. Patient was comfortably wearing the dentures. One-year follow up showed that there was minimal bone loss, dentures had good retention and functioning well.